The development of language - Gleason, Jean Berko; Ratner, Nan Bernstein (Allyn & Bacon communication sciences and disorders series, 2013)
Combining the contributions of experts and highly-respected researchers, this text offers a definitive exploration of language acquisition and development from infancy through adulthood. Taking a multi-disciplinary approach, it examines what we know about language development-addressing communication development in infancy, phonological development, semantic development, morphology and syntax. Broadening the scope of study, it puts language development into larger biological , social and cultural contexts, while investigating individual differences, atypical development, literacy and even language development in adults. This edition includes more on cross-linguistic language acquisition (emphasizing Spanish), new research on the nature and treatment of language disorders in children, and new perspectives on the impact of culture on language development and variation